Prevalence of workplace violence in Aceh, Indonesia: a survey study on hospital nurses - Putra, Ardia; Kamil, Hajjul; Adam, Muhammad; Usman, Said (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the work: Violence against healthcare professionals, especially nurses, is a severe issue that can have significant physical, psychological, and social impacts. It is essential to promptly document acts of violence and establish protocols and resources to prevent future incidents in healthcare facilities. This study aimed to collect data on both physical and non-physical violence against nurses in Aceh Province hospitals and identify the perpetrators. Research design and methods: The researcher utilized a cross-sectional methodology to investigate the entire population of nurses registered with the Regional Representative Council of the Indonesian National Nurses Association in Aceh Province, Indonesia. Information was collected through web-based surveys and facilitated by assigned enumerators in each district. Descriptive statistics were applied to analyze the data. Results: Last year, nurses working in Aceh Province hospitals documented multiple instances of workplace violence, such as physical assault (15%) and sexual abuse (5.5%), significantly affecting the well-being of nurses. A majority of nurses (64.4%) faced emotional abuse, while 37.9% encountered verbal threats and 10.4% experienced verbal sexual harassment. Notably, relatives/patients' families were identified as the main perpetrators, contributing to 60.3% of the reported incidents. Conclusions: Nursing associations are crucial in offering guidance, regulations, and educational resources related to workplace violence. This support is vital in promptly identifying and tackling potentially violent behaviors in the workplace, which ultimately helps in mitigating incidents of violence at work.